Organizational Success based on the Inter-Organizational Knowledge Sharing (IOKS) Perspective - Sudarnice, Sudarnice; Ekowati, Dian; Rialmi, Zackharia; Supriadi, Yudi Nur (Journal of Posthumanism, 2025)
This paper develops an IOKS (Inter-Organizational Knowledge Sharing) model to assist organizations in managing knowledge sharing effectively. The study conducts a systematic literature review of IOKS research from 2000 to 2024, analyzing 52 articles. It reveals that IOKS plays a vital role in knowledge management, enabling organizations to acquire knowledge from others, thus enhancing innovation performance. Key mechanisms for IOKS include alliances, professional networks, information technology, joint training, and employee exchanges, which foster strong relationships and improve learning capabilities. The success of IOKS is influenced by factors such as trust, open culture, shared goals, and collaboration incentives. These elements contribute to an innovative environment that supports knowledge sharing based on high absorptive capacity and innovation capabilities, driving organizational growth and performance.